The effects of low-volume HIIT and aerobic exercise on redox status parameters - Jamurtas, A.; Sakellariou, V.; Apostolopoulos, A.; Deli, C. K.; Georgakouli, K.; Fatouros, I. G.; Koutedakis, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Low volume, high-intensity interval training has been used recently in healthy trained individuals and patient populations. This type of training is characterized by high intensity that results in significant changes in ATP:ADP/AMP ratio and activation of key enzymes involved in metabolism. However, there are only few studies that examined the effects of this type of training on redox status modulation. Therefore, this study aimed to identify possible changes in redox status parameters and compare those to an aerobic exercise session. Methods: Twelve healthy young men participated in a randomized, cross-over design in two exercise sessions. In one of those sessions participants performed four 30 second sprints on a cycle ergometer interspersed with 4 min of recovery (HIIT). Resistance on the cycle ergometer was equivalent to 0.075 kg/kg of body mass. The aerobic exercise session consisted of cycling on a cycle ergometer for 30 minutes at an intensity corresponding to 70% of their predetermined VO2max. Blood was drawn before the exercise, immediately post, 24, 48 and 72 hours post-exercise and was analyzed for thiobarbituric acid reactive substances (TBARS), catalase activity and total antioxidant capacity (TAC). Results: A significant group x time interaction was found for TAC. HIIT resulted in significant (p<.001) increases in TAC immediately post and 24 hours post exercise whereas aerobic exercise resulted in significant (p<.001) increases in TAC only immediately post exercise. Furthermore, catalase levels were significantly higher immediately post (p<.05) and 24 hours (p<.001) post exercise in HIIT compared to aerobic exercise. No significant changes (p>.05) were observed for TBARS and catalase following neither exercise session. Conclusion: HIIT results in significant changes in antioxidant status that lasts for 24 hours post exercise and these changes seem to be higher compared to aerobic exercise. Further research should examine more redox status indices following HIIT as well as attempt to delineate the reasons behind the aforementioned changes.